PEMBERDAYAAN PEMERINTAH DAERAH KABUPATEN INDRAGIRI HILIR TERHADAP KELOMPOK TANI DI KELURAHAN KEMPAS JAYA KECAMATAN KEMPAS TAHUN 2019 - Rosa Kartika Ayu; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Empowerment of farmer groups aims to develop a mindset and work of farmers whose processes are continuously carried out by the government. The government as an agent of empowerment must know and be able to adopt new innovations in order to create farmer welfare. The background of this thesis is the researcher's view of the phenomena that occur in the assessment of the ability of farmer groups in the Kempas Jaya Village. There are four farmer groups in the 2019 assessment process down to the advanced class which was previously the main class. With the formulation of the problem in this study are how and what factors are hindering the empowerment of the local government of Indragiri Hilir Regency against farmer groups in the Kempas Jaya Village, Kempas District in 2019. This research aims to describe the empowerment of local governments towards farmer groups and identify factors that hinder government empowerment. Indragiri Hilir Regency to farmer groups in the Kempas Jaya Village, Kempas District in 2019.The research approach used is a qualitative approach. This type of research is descriptive. The research location is in the Kempas Jaya Village, Kempas District, Indragiri Hilir Regency. With the type and source of research data is divided into primary data in the form of purposive informant retrieval techniques and secondary data in the form of supporting data related to farmer groups. Data collection techniques used interviews and documentation, while data analysis was carried out using qualitative analysis.The results of this study indicate that the Local Government of Indragiri Hilir Regency has been able to empower farmer groups through several empowerment programs in four forms, namely human development, business development, environmental development and institutional development. However, in implementing the empowerment efforts of the Indragiri Hilir District Government to the farmer groups of the Kempas Jaya Village, they experience internal constraints from the lack of means of production, lack of institutional strengthening, and low knowledge of farmers, and constraints from external geographical conditions and extension workers. Keywords: Empowerment, Farmer Groups, Local Government